EVALUSASI KEBIJAKAN SUBSIDI KUOTA (STUDI KASUS DI FISIP UPN VETERAN JAWA TIMUR) - Kurnia Adhi Yaksa; Satria Surya Amando; Lukman Arif (Jurnal Penelitian Administrasi Publik, 2021)
The impact of the Covid-19 pandemic affects changes in human behavior that are wider over a longer period of time. This also has an impact on the system Deducation in Indonesia. Teachers, teachers, lecturers and students will get used to doing distance learning interactions. East Java National Development University implement a Distance Learning (PJJ) policy for all teachers and students, in order to stop the spread of the Covid-19 virus. The government has been providing quota assistance for the community to support distance learning activities (PJJ) which are divided into two types, namely quotas for the public that can be used to access all pages and applications and study quotas are only for accessing appropriate pages and applicationse rgistered with the Ministry of Education and Culture. This study aims to evaluate the implementation of secretary general regulation number 4 of 2021 regarding quota assistance subsidies, whether This program is running well as intended. The method used in this research is a qualitative exploration with student informants in the Department of Public Administration. Based on the results of the study, it can be seen that the free quota given from Ministry of Education and Culture specifically for applications: Vclass, Unsil meet, zoom, whatsapp, google classroom.In terms of implementation, it is still classified as uneven in distribution and there are some delay. Some of these reasons make students dissatisfied in receiving this quota assistance. We are hereby moved to carry out this research.